Early postoperative feeding with elemental diet. Issue 6159 (3rd February 1979) - Sagar, S; Harland, P; Shields, R
Abstract : The value of early postoperative feeding with an elemental diet was assessed in 30 patients after major gastrointestinal operations. The patients were allocated at random to conventional treatment (control group) or feeding with the elemental diet (ED group). The clinical and metabolic course of the 15 patients in the ED group was significantly better than that of the controls. Patients in the ED group lost less weight and had a shorter stay in hospital. Negative nitrogen balance was more pronounced in the control group throughout the seven postoperative days. Energy intake was higher in the ED group. Provided elemental feeding is used with caution, it may be given from the first postoperative day. Patients do better metabolically and require shorter stays in hospital.